1983
DOI: 10.1111/j.1432-1033.1983.tb07288.x
|View full text |Cite
|
Sign up to set email alerts
|

Metallothionein Synthesis in Foetal, Neonatal and Maternal Rat Liver

Abstract: The synthesis of hepatic metallothionein relative to other cytosol proteins was measured by [35S]cysteine incorporation in foetal, neonatal and pregnant rats. The relative rate of hepatic metallothionein synthesis reached a maximum in foetal liver on days 18 -21 of gestation. Metallothionein synthesis then declined until weaning, when adult levels were established. The rate of metallothionein synthesis was greater in pregnant rats at term than in nulliparous rats.To determine if circulating inducing agents cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
5
1

Year Published

1986
1986
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(9 citation statements)
references
References 47 publications
3
5
1
Order By: Relevance
“…The higher MT levels in kidney than liver on day 7 would thus indicate differences in posttranscriptional regulation in these two organs. This is in agreement with the observations on Antarctic icefish and the developmental MT regulation in rat [25, 29, 30]. Further studies are necessary to clarify the mechanisms regulating the observed differences in posttranscriptional regulation of MT in fish.…”
Section: Discussionsupporting
confidence: 91%
“…The higher MT levels in kidney than liver on day 7 would thus indicate differences in posttranscriptional regulation in these two organs. This is in agreement with the observations on Antarctic icefish and the developmental MT regulation in rat [25, 29, 30]. Further studies are necessary to clarify the mechanisms regulating the observed differences in posttranscriptional regulation of MT in fish.…”
Section: Discussionsupporting
confidence: 91%
“…These dolphins are the result of spontaneous abortions, and being these relevant situations of stress, probably it was the cause of the lack of a defined pattern regarding adult females of this group geographic. In relation to the pregnant female, coincidentally with previous studies in pregnant women (Mc Ardle and Ashworth, 1999) and rats (Piletz et al, 1983), MT concentrations are higher than nonpregnant females.…”
Section: Discussionsupporting
confidence: 59%
“…For instance, it has been shown that in itro translation of polyribosomal mRNA from Cd-treated rats did not consistently give greater synthesis of MT protein than that from control rats [28]. In addition, studies of rat development have shown that, after birth, total MT-1 and MT-2 mRNA levels remained high, although MT protein levels [12,13], and MT synthesis rates [29], decreased. Furthermore, during the induction of MT by Zn, MT mRNA levels remained higher than control values for up to 36 h, whereas the rate of synthesis of MT was the same as the control by 24 h [30].…”
Section: Discussionmentioning
confidence: 95%